Strategy of Development Production System in The Food Plan Section At PT. Benih Citra Asia – Indonesia - Siswanto, Adil; Mahendra, Muhammad Hadyanshah; Mas’ Ud, Ahmad Ibnu (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study investigates the strategic development of the production system within the Food Plant section at PT. Benih Citra Asia, a leading agricultural seed company in Indonesia. The research aims to identify and analyze current operational inefficiencies and to propose a sustainable, productivity-oriented development strategy aligned with modern agribusiness practices. Method: Employing a qualitative-descriptive method supported by SWOT analysis and the Value Stream Mapping (VSM) approach, the study evaluates internal capabilities, external challenges, and the alignment of technological integration with production workflows. Data were collected through in-depth interviews with key management personnel, direct field observations, and document analysis. Practical Applications: The findings reveal several bottlenecks in seed processing, quality control, and inventory management, primarily stemming from outdated machinery, inconsistent labor skills, and suboptimal layout design. The proposed strategy emphasizes lean production principles, digital monitoring systems, and capacity-building programs to enhance operational efficiency and output quality. This strategic model is expected to significantly improve production scalability, reduce waste, and strengthen PT. Benih Citra Asia’s competitive advantage in the national and regional seed markets. Conclusion: The study contributes to the literature on agribusiness management by offering a contextualized framework for developing production systems in Indonesia's agricultural sector.